PERSEPSI KENYAMANAN PARA PENGHUNI ASRAMA POLISI DI LEMBAGA PENDIDIKAN DAN PELATIHAN KEPOLISIAN REPUBLIK INDONESIA â€“ AKADEMI KEPOLISIAN - Hartawan, Varian Dedy; Setyowati, Erni; Suprapti, Atik (MODUL, 2019)
As a primary need, shelter or boards are often to the top priority in human life which must be fulfilled after clothing and food. TheÂ  Police Dormitory from Indonesian Republic Police Education And Training Institutions â€“ Police Academy or abbreviated in Indonesian â€œLemdiklat Polri â€“ Akpolâ€Â  is residential facility in the police dormitory provided for personnel and staff who teach or served in the Police Academy both members of the National Police or PNS (Goverment Employees). Â Not infrequently this dormitory are also inhabited more than two years by its members who serve in the Indonesian Republic Police Education And Training Instituitions â€“ Police Academy. The majority of residents can be said to be decent enough to buy, or rent and inhabit outside the plice dormitory which has far better conditions than the police dormitory itself. This paper aims to determine the factors that make them stay at home to live there, even thought they can rent or buy more suitable home to live. The method used is mixing of qualitative methods and quantitative methods called mixed methods, and also look at the psychological and economic aspects of them. The results of the study reveal that there are a numbers of reasons for neighboring life that are safe, comfortable, economically affordable, the tranquility and natural silence in the surrounding area along with pollution â€“ free air makes the residents still remain even though this location is far from the economic center in mainly.